Resolving the Dual Yā Orthographic Variation in Pashto: An Interdisciplinary Approach Integrating Linguistic, Technological, and Educational Perspectives in Afghanistan and Pakistan - Inamullah Malal; Sayed Sharif Ahmad Lalakhil (Penerbit Hellow Pustaka, 2025)
Pashto, a major language in Afghanistan and Pakistan, faces persistent orthographic inconsistencies regarding the dual graphemes Yā (